Design of Savana Hills Ecotourism Tracking Route in Pulisan Village, Likupang Regency, North Minahasa - Bet El Silisna Lagarense; Mex Usmeni Pesik; Agustinus Walansendow (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The community service program with the students focuses on Pulisan Village, which is in the Likupang KEK (Special Economic Zone) area and a super-priority tourism destination. Pulisan has many attractions, including beaches, islands, and sea. However, Pulisan also needs new tourist attractions, specifically terrestrial tourist attractions, to distribute tourist visits well. Therefore, a community service program with students is carried out in collaboration with partners, namely tourism care groups entitled Designing the Savana Hill Ecotourism Tracking Route in Pulisan Village, Likupang, North Minahasa Regency. The method used was direct assistance to the community, in this case, the Pulisan Village tourism awareness group responsible for developing the Pulisan Tourism Village. The design of the ecotourism tracking route used mapping technology to determine the direction and location points created, as well as stopping points along the Pulisan Savana Hill tracking route. With the Savana Hill tracking route, tourist visits are focused on the sea, islands, and beaches, and they are distributed to Savana Hill using the designed tracking route. The community service program with students resulted in an output, namely the design of a tracking route with three stopping points (shelters).